Repurposing carvacrol, cinnamaldehyde, and eugenol as potential anti-quorum sensing agents against uropathogenic Escherichia coli isolates in Alexandria, Egypt - Hadeer A. Morgaan; Hoda M. G. Omar; Azza S. Zakaria; Nelly M. Mohamed (BMC Microbiology, 2023)
Abstract Background Urinary tract infections represent one of the most frequent hospital and community-acquired infections with uropathogenic Escherichia coli (UPEC) being the main causative agent. The global increase in the emergence of multidrug-resistant (MDR) UPEC necessitates exploring novel approaches. Repurposing natural products as anti-quorum sensing (QS) agents to impede bacterial virulence is gaining momentum nowadays. Hence, this study investigates the anti-QS potentials of carvacrol, cinnamaldehyde, and eugenol against E. coli isolated from urine cultures of Egyptian patients. Results Antibiotic susceptibility testing was performed for 67 E. coli isolates and 94% of the isolates showed MDR phenotype. The usp gene was detected using PCR and accordingly, 45% of the isolates were categorized as UPEC. Phytochemicals, at their sub-inhibitory concentrations, inhibited the swimming and twitching motilities of UPEC isolates, with eugenol showing the highest inhibitory effect. The agents hindered the biofilm-forming ability of the tested isolates, at two temperature sets, 37 and 30 °C, where eugenol succeeded in significantly inhibiting the biofilm formation by > 50% at both investigated temperatures, as compared with untreated controls. The phytochemicals were shown to downregulate the expression of the QS gene (luxS) and critical genes related to motility, asserting their anti-QS potential. Further, the combinatory activity of the phytoproducts with five antibiotics was assessed by checkerboard assay. The addition of the phytoproducts significantly reduced the minimum inhibitory concentrations of the antibiotics and generated several synergistic or partially synergistic combinations, some of which have not been previously explored. Conclusions Overall, carvacrol, cinnamaldehyde, and eugenol could be repurposed as potential anti-QS agents, which preferentially reduce the QS-based communication and attenuate the cascades of gene expression, thus decreasing the production of virulence factors in UPEC, and eventually, subsiding their pathogenicity. Furthermore, the synergistic combinations of these agents with antibiotics might provide a new perspective to circumvent the side effects brought about by high antibiotic doses, thereby paving the way for overcoming antibiotic resistance.